Phytochemical Compounds and Biological Activities of Celtis tournefortii Fruits - Keser, Serhat; Keser, Fatma; Kaygili, Omer; Tekin, Suat; Turkoglu, Ismail; Demir, Ersin; Kirbag, Sevda (Taylor and Francis Ltd., 2017)
It is known that Celtis species have been used in healing wound, epilepsy crisis, and stomach pain among the people. The antiradical (DPPH, OH, ABTS) activities, phytochemical compounds (total proanthocyanidin, total flavonoid, total phenolic, flavonoids, phenolic acids, sterols, lipid soluble vitamins, fatty acids), antimicrobial, antiproliferative (MCF-7, HCT-116, A2780, PC-3) activities of water, ethanol, methanol extracts of C. tournefortii fruits were evaluated in this study. All the C. tournefortii fruit water extracts were higher scavenged OH radical than standard antioxidant BHT. It was detected that C. tournefortii includes high amount of ?-tocopherol (2.65 mg/kg), vitamin D (10.05 mg/kg), ergosterol (78.70 mg/kg), stigmasterol (185.90 mg/kg), unsaturated fatty acids (74.47%). C. tournefortii extracts showed antiproliferative activity on MCF-7, HCT-116, A2780, PC-3 cancer cell lines and antimicrobial activity on some microorganisms when compared to standard antibiotics. Also, this study is the first report about phytochemical contents, antiproliferative, antimicrobial, antiradical properties of C. tournefortii fruits. © 2017 Har Krishan Bhalla & Sons.
Keywords: ABTS; antimicrobial; antiproliferative; Celtis tournefortii; OH; phytochemical